Metformin improves endothelial function in type 1 diabetic subjects: a pilot, placebo‐controlled randomized study. Issue 5 (5th December 2012) - Pitocco, D.; Zaccardi, F.; Tarzia, P.; Milo, M.; Scavone, G.; Rizzo, P.; Pagliaccia, F.; Nerla, R.; Di Franco, A.; Manto, A.; Rocca, B.; Lanza, G. A.; et al.
<x xml:space="preserve">Abstract</x> Aims Several studies have investigated the effects of metformin treatment in patients with type 1 diabetes mellitus (T1DM). No study has hitherto examined its effects on endothelial function in these patients. In this study we sought to evaluate the effect of metformin on endothelial function in type 1 diabetic patients. Methods Forty‐two uncomplicated T1DM patients were randomized in a placebo‐controlled, double‐blind, 6‐month trial to treatment with either metformin or placebo. Glycometabolic and clinical parameters as well as flow‐mediated dilation (FMD) and nitrate‐mediated dilation (NMD) of the right brachial artery were measured at baseline and at the end of the study. Glycaemic variability (GV, calculated from continuous glucose monitoring data) and a biomarker of oxidative stress [urinary 8‐iso‐prostaglandin F2α (PGF2α)] were also assessed. Results Baseline data were similar in the two groups. Compared with placebo, metformin significantly reduced body weight [−2.27 kg (95% confidence interval: −3.99; −0.54); p = 0.012] whilst improved FMD [1.32% (0.30; 2.43); p = 0.013] and increased PGF2α [149 pg/mg creatinine (50; 248); p = 0.004]. Notably, the improvement of FMD did not correlate with the decrease of body weight (r2 < 1%). NMD, haemoglobin A1c, GV, daily insulin dose and other parameters did not significantly change after the treatment comparing the two groups. Conclusions Our pilot trial showed that, in uncomplicated type 1 diabetic subjects, metformin improved FMD and increased PGF2α, a marker of oxidative stress, irrespective of its effects on glycaemic control and body weight. Randomized, blinded clinical trials are needed to evaluate the benefits and risks of metformin added to insulin in type 1 diabetes.